Rare Complication of Cardiopulmonary Resuscitation-Liver Injury - Hoskovec, David; Klobušický, Pavol; Pudlač, Adam; Lochman, Matyáš; Krška, Zdeněk; Dytrych, Petr (Medicina (Kaunas, Lithuania), 2024)
Background and Objectives: Liver injury is a rare complication of cardiopulmonary resuscitation. Correct and early diagnosis and treatment are essential. The clinical signs of injury may be masked by the cardiac arrest. We present a single-centre retrospective observational study of traumatic liver injury after cardiopulmonary resuscitation. Materials and Methods: A retrospective analysis of the patients treated for liver injury after cardiopulmonary resuscitation was conducted. Demographic data, the cause of resuscitation, the duration of restoration of spontaneous circulation (ROSC), and the surgical approach were analysed. Results: We have treated nine patients with severe liver injury after cardiopulmonary resuscitation. The diagnosis was made on the basis of cardiopulmonary instability, a fall in the erythrocyte count in eight cases, and was confirmed by CT or ultrasound examination. The last one was diagnosed accidentally on MR. Surgery, in cases of unstable patients, was followed immediately after a diagnosis. We combined liver sutures and intra-abdominal packing with a planned second-look surgery. Five of the nine patients survived. Conclusions: Liver injury after cardiopulmonary resuscitation is rare and is associated with high mortality. The recurrence of cardiopulmonary instability and/or a low or falling red blood cell count are the main signs of this injury. Bedside ultrasound and CT scans are the most important methods to confirm the diagnosis. The rule of surgical repair is the same as in all liver injuries, regardless of aetiology. The key factors for survival include early diagnosis, together with the length of restoration of spontaneous circulation (ROSC).
Keywords: senioři; Liver; liver injury; Heart Arrest; játra; srdeční zástava; Retrospective Studies; automated compression device; ROSC; Cardiopulmonary Resuscitation; Middle Aged; mužské pohlaví; Adult; cardiopulmonary resuscitation; kardiopulmonální resuscitace; ženské pohlaví; retrospektivní studie; Humans; lidé středního věku; dospělí; Female; Aged; lidé; Male